Successful Milk Oral Immunotherapy Promotes Generation of Casein-Specific CD137+ FOXP3+ Regulatory T Cells Detectable in Peripheral Blood - Zhang, Yi; Li, Lei; Genest, Geneviève; Zhao, Wei; Ke, Dan; Bartolucci, Sabrina; Pavey, Nils; Al-Aubodah, Tho-Alfakar; Lejtenyi, Duncan; Torabi, Bahar; Ben-Shoshan, Moshe; Mazer, Bruce; et al. (Frontiers in Immunology, 2021)
BACKGROUND: Oral immunotherapy (OIT) is an emerging treatment for cow’s milk protein (CMP) allergy in children. The mechanisms driving tolerance following OIT are not well understood. Regulatory T cells (TREG) cells are key inhibitors of allergic responses and promoters of allergen-specific tolerance. In an exploratory study, we sought to detect induction of allergen-specific TREG cells in a cohort of subjects undergoing OIT. METHODS: Pediatric patients with a history of reactions to cow’s milk, positive Skin Pick Test (SPT) and/or CMP-specific IgE >0.35 kU, and a positive oral challenge to CMP underwent OIT with escalating doses of milk and were followed for up to 6 months. At specific milestones during dose the escalation and maintenance phases, casein-specific CD4+ T cells were expanded from patient blood by culturing unfractionated PBMCs with casein in vitro. The CD4+ T cell phenotypes were quantified by flow cytometry. RESULTS: Our culture system induced activated casein-specific FOXP3+Helios+ TREG cells and FOXP3- TEFF cells, discriminated by expression of CD137 (4-1BB) and CD154 (CD40L) respectively. The frequency of casein-specific TREG cells increased significantly with escalated doses of milk during OIT while casein-specific TEFF cell frequencies remained consistent. Moreover, expanded casein-specific TREG cells expressed higher levels of FOXP3 compared to polyclonal TREG cells, suggesting a more robust TREG phenotype. The induction of casein-specific TREG cells increased with milk tolerance and correlated with increased frequencies of casein-specific Th1 cells among OIT subjects. The level of casein-specific TREG cells negatively correlated with the time required to reach the maintenance phase of desensitization. CONCLUSIONS: Overall, effective CMP-OIT successfully promoted the expansion of casein-specific, functionally-stable FOXP3+ TREG cells while mitigating Th2 responses in children receiving OIT. Our exploratory study proposes that an in vitro TREG response to casein may be useful in predicting time to reach maintenance in CMP-OIT.